ADVANTAGES OF TARGET CONTROL INFUSION - TOTAL INTRAVENOUS ANESTHESIA VS SEVOFLURANE INHALATION ANESTHESIA IN CONTROLLING SURGERY - RELATED STRESS RESPONSE - Lleshi, Albert; Gavrilovska Brzanov, Aleksandra; Kiprijanovska, Biljana; Ognjanova Simjanovska, Violeta; Trposka, Angela; Mladenovska Cvetkova, Marija (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2024)
Introduction: The stress response to surgery, a sequence of pathological and physiological alterations brought on by the stimulation of surgery, can be divided into two main categories: the inflammatory-immune response and the neuroendocrine-metabolic response. It depends on the anesthesia technique and surgical approach. Material and Methods: The patients were divided into two groups: Sevoflurane inhalational anesthesia (SIA) and Target control infusion-Total intravenous anesthesia (TCI-TIVA). The TCI-TIVA group has used the Marsh model for the propofol and the Minto model for the remifentanil, using target plasma concentration. The SIA group has induction in general anesthesia with Propofol plus Fentanyl, and the maintenance of anesthesia has been achieved with Sevoflurane on MAC 0.7-1.0. We compared the effect of different anesthetic techniques on the surgical stress response through measuring the blood levels of proinflammatory cytokines Interleukin-6, Cortisol and blood glucose, as well as the hemodynamic response. Results: Interleukin-6 (IL-6) levels rise sharply from T0 (4.78εg/mL) to T2 (10.06εg/mL) and then again at T3 (36.34εg/mL), showing a strong inflammatory response after surgery in the SIA group. IL-6 levels in the TCI-TIVA Group exhibit a comparable pattern, however with a significantly smaller increase at T3 (14.56). When comparing the cortisol levels at T0, both groups show a comparable range of variability. There is a highly significant difference in cortisol levels between TIVA and SIA after extubating and 24 hours postoperatively, as indicated by the T2 p-value of less than 0.001. Glucose levels in the SIA group are comparatively constant from T0 (5.29) to T1 (5.25), then they significantly rise at T2 (6.56) and stay high at T3 (5.71). Glucose levels in the TCI-TIVA Group exhibit less variability, increasing slightly from T0 (5.17) to T2 (5.21) and then staying constant at T3 (5.28). Hemodynamic stability was better with TCI-TIVA than with SIA. Conclusion: Our findings indicate that TCI-TIVA consistently demonstrates advantages regarding controlling the stress response, inflammation, and metabolic response both during and after surgery as compared to the SIA group. These results provide credence to the prospective advantages of TCI-TIVA over SIA in surgical settings where patient’s outcomes depend critically on reducing stress, inflammation, and metabolic disturbances
Keywords: Blood glucose; Cortisol; Interleukin-6; Sevoflurane inhalational anesthesia; Stress response; Total intravenous anesthesia-target controlled infusion